Dirhodium Caprolactamate Catalyzed Alkoxyalkylation of Terminal Alkynes - Tusun, Xiarepati; Lu, Chong-Dao (Synlett, 2013)
Dirhodium caprolactamate [Rh2(cap)4] effectively catalyzes alkoxyalkylation of terminal alkynes in the presence of tert-butyl hydroperoxide (TBHP) under mild conditions.
Keywords: alkoxyalkylation; alkynes; catalysis; dirhodium(II)